Factors associated with nonresponse to ovulation induction using letrozole among women with World Health Organization group II anovulation - Thilina Sanjeewa Palihawadana; Prasantha Sudehana Wijesinghe; Harshalal Rukka Seneviratne (Wolters Kluwer Medknow Publications, 2015)
Context: Letrozole, a third generation aromatase inhibitor is gaining importance in ovulation induction. Some prefer to use it as a second line agent in women who fail to respond to clomifene citrate. However, our knowledge about the predictors of response to letrozole is limited. Aims: The study was aimed at identifying the factors associated with letrozole resistance among women with World Health Organization (WHO) group II anovulation. Subjects and Methods: Study was conducted at the infertility clinic at a tertiary care hospital in Sri Lanka. A case-control study design was used and included 50 subjects with WHO group II anovulation (25 clomifene responsive and 25 clomifene resistant). After a treatment cycle of letrozole, the factors were compared between the subjects who responded and those who failed to respond to treatment. Results: Ovulation was achieved in 76% (n = 19) of subjects who had responded to clomifene previously and in 24% (n = 6) with clomifene resistance. The factors associated with letrozole resistance included the presence of hirsutism (odds ratio [OR]: 3.89; 95% confidence interval [CI]: 1.2-12.3) and clomifene resistance (OR: 10.03; 95% CI: 2.81-35.7). The early follicular phase mean (standard deviation) luteinizing hormone level was significantly higher among the nonresponders (9.75 [4.78] - 7.28 [2.3]; P = 0.02). Nonresponders showed significantly lower levels of oestradiol on the 5 th and 9 th days (28.50 [3.39] pg/mL vs. 7.49 [3.62] pg/mL; P = 0.0007 and 142.04 [76.22] pg/mL vs. 28.10 [12.8] pg/mL; P = 0.0001) of the menstrual cycle, respectively. Conclusions: The features associated with resistance to Letrozole at a dose of 2.5 mg show some overlap with those associated with clomifene resistance. However, some features do not show similar association. The effectiveness of letrozole at a dose of 2.5 mg in induction of ovulation among women with clomifene resistance is low and it does not seem to be a suitable treatment at a dose of 2.5 mg for this indication.